Efektivitas Pengembangan Media Interaktif Berbasis Smart Application Creator Materi Menulis Teks Narasi di Kelas IV Sekolah Dasar - Nanda Puspa Gemalla; Masniladevi Masniladevi (Universitas Negeri Padang, 2025)
The research was motivated by the lack of variation in the use of IT-based media, especially material for writing narrative texts. The aim of the research is to develop interactive media based on Smart Application Creator, material for writing narrative texts in class IV elementary school that is effective. This type of research is development research using the ADDIE model. The school is the test subject of SD Negeri 114/VI Bangko VII and the research subject of SD Negeri 115/VI Bangko VIII. The media is validated through a validity questionnaire assessed by material, media and language experts. Test the practicality of the media through teacher response questionnaires and student questionnaires. The effectiveness test is obtained from the results of the test questions. The media is very valid with an average rating from validators of 94%. The media is very practical, from the average practicality questionnaire results for teachers, 95.71% and students, 95.14%. The effectiveness results show an increase, the average score of test school students is 83.97%, research school 90.20%. Based on the results, it has been proven that the SAC interactive media, material for writing narrative texts, has been declared effective for use in learning.